New Properties on Degenerate Bell Polynomials - Taekyun Kim (Hindawi-Wiley, 2021)
The aim of this paper is to study the degenerate Bell numbers and polynomials which are degenerate versions of the Bell numbers and polynomials. We derive some new identities and properties of those numbers and polynomials that are associated with the degenerate Stirling numbers of both kinds.